Development of High Performance Thin Layer Chromatographic Method for Simultaneous Estimation of Atenolol and Nefidipine in Combined Dosage Form - Ramteke, Madhuri; Kasture, Avinash; Dighade, Narendra (Asian Journal of Chemistry, 2010)
An accurate and precise high pressure thin layer chromatographic method for simultaneous estimation of atenolol and nefidipine in their combined dosage form has been developed. The study employs kieselghur 60, GF254 on aluminium foil and a mobile phase comprising cyclohexane:methanol:ethyl acetate:ammonia (5:1.5:3:0.5 v/v). The detection was carried out at 230 nm. The linear detector response for atenolol was observed between 5.7-18.9 μg/mL while for nifedipine 2.3-7.0 μg/mL. The recovery study was carried out by standard addition method. The results of recovery were 99.76 ± 0.216, 100.72 ± 0.216 for atenolol and 100.04 ± 1.069, 99.89 ± 1.058 for nifedipine.